Multiple cellular proteins interact with LEDGF/p75 through a conserved unstructured consensus motif - Tesina, Petr; Čermáková, Kateřina; Hořejší, Magdalena; Procházková, Kateřina; Fábry, Milan; Sharma, Subhalakshmi; Christ, Frauke; Demeulemeester, Jonas; Debyser, Zeger; Rijck, Jan De; Veverka, Václav; Řezáčová, Pavlína (Nature communications, 2015)
Lens epithelium-derived growth factor (LEDGF/p75) is an epigenetic reader and attractive therapeutic target involved in HIV integration and the development of mixed lineage leukaemia (MLL1) fusion-driven leukaemia. Besides HIV integrase and the MLL1-menin complex, LEDGF/p75 interacts with various cellular proteins via its integrase binding domain (IBD). Here we present structural characterization of IBD interactions with transcriptional repressor JPO2 and domesticated transposase PogZ, and show that the PogZ interaction is nearly identical to the interaction of LEDGF/p75 with MLL1. The interaction with the IBD is maintained by an intrinsically disordered IBD-binding motif (IBM) common to all known cellular partners of LEDGF/p75. In addition, based on IBM conservation, we identify and validate IWS1 as a novel LEDGF/p75 interaction partner. Our results also reveal how HIV integrase efficiently displaces cellular binding partners from LEDGF/p75. Finally, the similar binding modes of LEDGF/p75 interaction partners represent a new challenge for the development of selective interaction inhibitors.
Keywords: proteiny vázající RNA; konsenzuální sekvence; Humans; protoonkogenní protein MLL; proteiny; HIV-integrasa; Transcription Factors; Molecular Sequence Data; dimerizace; Proteins; molekulární sekvence - údaje; Histone-Lysine N-Methyltransferase; Escherichia coli; Lentivirus; Dimerization; lidé; Transposases; transposasy; Intercellular Signaling Peptides and Proteins; represorové proteiny; Amino Acid Sequence; Myeloid-Lymphoid Leukemia Protein; Repressor Proteins; Consensus Sequence; mezibuněčné signální peptidy a proteiny; histonlysin-N-methyltransferasa; transkripční faktory; HIV Integrase; terciární struktura proteinů; RNA-Binding Proteins; Protein Structure, Tertiary; sekvence aminokyselin